Ultrasound Archiving in the Emergency Department: Implementation, Governance and 4‐Year Outcomes at an Australian Tertiary Emergency Department - Vijay Manivel; Behzad Mirmiran; Claire Helm; Cindy Hastings (Emergency Medicine Australasia, 2026)
ABSTRACT Objective Image archiving is one of the least developed aspects of emergency department ultrasound (ED‐US) in Australasia, despite its recognised role in governance, education, quality assurance (QA) and medicolegal protection. A middleware‐based ED‐US image workflow solution was installed at Nepean Hospital ED in October 2021. We describe our implementation and 4‐year experience with a dedicated ED‐US archiving solution at a tertiary Australian ED. Methods Single‐centre retrospective analysis of service implementation, technical requirements, governance, QA and operational outcomes over a 4‐year period. Results Archived 7281 ED‐US studies across 15 modalities between October 2021 and April 2026, with annual volume growing from 1083 (2022) to 2224 (2025). Bidirectional EMR connectivity, worklist generation, seamless DICOM image transfer, segregation of clinical from educational studies, structured reporting, interdepartmental image access, automated trainee logbooks and structured QA review are implemented. No failures occurred, and no data were lost. Costs of implementation and maintenance depend on vendor negotiation and local IT costings; the dominant recurring cost is clinician time, not software. The most challenging aspects were IT resource allocation, multivendor integration and governance workload. The automated logbook alone saves each trainee approximately 2 h/week. No medicolegal incidents were reported. Conclusions A structured ED‐US archive and workflow are achievable and sustainable in an Australian tertiary ED. In our case, it strengthened accountability, quality of scans, education, research, interdepartmental collaboration and institutional risk management. Our experience provides Australasian EDs with a practical starting point for planning their own implementation.